Formal credit constraint and prevalence of reciprocal loans in rural China - Jianmei Zhao (Open Economics, 2021)
The unique feature of the rural credit market in China is the dominance of zero collateral and zero-interest reciprocal lending and its long-term coexistence with the formal loan. This paper investigates the association between formal credit constraint and prevalence of reciprocal loans in rural China. Based on the identification of rural households' credit constraint status, we examine the effects of credit constraint on the utilization of informal reciprocal loans. We find that formal credit constraint significantly increases rural borrowers' reliance on reciprocal loans, whereas the "debt of gratitude" imposes an uncertain obligation on rural borrowers, and discourages them from borrowing amongst relatives and friends.
Keywords: Q12; O14; Q18; 330; credit constraint; reciprocal loan; debt of gratitude; sample selection